2021
DOI: 10.3390/polym13203553
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Hot-Pressed Polyamide 11 and 12: Mechanical, Thermal and Durability Properties

Abstract: Chemically speaking, polyamide 11 (PA11) and polyamide 12 (PA12) have a similar backbone, differing only in one carbon. From an origin point of view, PA11 is considered a bioplastic polyamide composed from renewable resources, compared to oil-based PA12. Each of them has a number of advantages over the other, which makes their selection a challenging issue. Depending on the target application, diverse assessments and comparisons are needed to fulfill this mission. The current study addresses this research gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 87 publications
(92 reference statements)
2
28
0
Order By: Relevance
“…Bahrami et al [ 29 ] reported large differences in the tensile behaviors of PA11 and PA12 polymers. While PA11 exhibited a quasi-brittle behavior, PA12 demonstrated a highly ductile behavior, showing a higher tensile strength, Young’s modulus, and strain at failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahrami et al [ 29 ] reported large differences in the tensile behaviors of PA11 and PA12 polymers. While PA11 exhibited a quasi-brittle behavior, PA12 demonstrated a highly ductile behavior, showing a higher tensile strength, Young’s modulus, and strain at failure.…”
Section: Resultsmentioning
confidence: 99%
“…Two commercially available thermoplastic polymeric resins were selected and used as matrices in the shape of pellets, namely, PA11 and PA12, both of which were provided by Arkema (Barcelona, Spain). These polyamides were selected due to their relatively low melting points, which leads to lower energy consumption during production and to their outstanding mechanical properties, including high tensile strength, high impact and fatigue resistance, high chemical and aging resistance, and low moisture absorption [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The nylon-6 particles labeled with NR and ATRB showed similar absorption bands distinctive of the polymer; however, the bands associated with the fluorescent molecule were absent ( Figure S6 , ESI†). For nylon-11 NPs, the characteristic absorption bands include 3301 cm −1 and 2919 cm −1 (N–H stretch), 2851 cm −1 (C–H vibration of the methylene groups), 1638 cm −1 (amide I), 1546 cm −1 (amide II), and 1467 cm −1 (C–H bending) [ 74 , 75 ]. The incorporation of NR and ATRB within the nylon-11 NPs did not result in detectable absorption bands from the fluorophore ( Figure S6 , ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, as the Figure 7, the tensile section of cPA was observed by SEM. Some cPAs with rich hydrogen‐bonding networks exhibited complex and large‐scale cracks on the tensile section, these cracks enable the ability of cPAs to withstand large deformations without breaking easily, which was related to the delay and redistribution of the accumulation of local stress by flexible hydrogen bonds 22,26,27 . Especially for the stretch curve of BH37, three distinct regimes of tensile modulus were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Some cPAs with rich hydrogen-bonding networks exhibited complex and large-scale cracks on the tensile section, these cracks enable the ability of cPAs to withstand large deformations without breaking easily, which was related to the delay and redistribution of the accumulation of local stress by flexible hydrogen bonds. 22,26,27 Especially for the stretch curve of BH37, three distinct regimes of tensile modulus were observed. The first regime was the linear elastic region at initial strain (ε < 2%), and the stress increased rapidly with increasing strain.…”
Section: Tensile Properties Of Synthesized Cpasmentioning
confidence: 97%